Band crossings and band terminations in rapidly rotating nuclei - Ragnarsson, Ingemar; Bengtsson, Tord (Nuclear Physics, Section A, 1986)
Predictions on terminating configurations in nuclei with 10-12 valence particles outside the 146Gd core are compared with recent experimental data. Observed and calculated spectra show a remarkable similarity, at least for 158Er and 156Er which nuclei are discussed in detail here.